Aphrodite's Kephali : an early Minoan I defensive site in Eastern Crete - Betancourt, Philip P. (Prehistory monographs, 2013)
Machine generated contents note:INTRODUCTION --1.Introduction, Philip P. Betancourt --2.The Isthmus of Ierapetra, Philip P. Betancourt --3.Geology and Geologic History, Floyd W. McCoy --4.The FN/EM I Settlement Patterns in the Northern Part of the Isthmus of Ierapetra, Philip P. Betancourt --5.The FN/EM I Settlement Patterns in the Southern Part of the Isthmus of Ierapetra, Kostas Chalikias --THE EVIDENCE --6.The Excavation of the Site, Philip P. Betancourt --7.The Architecture, Philip P. Betancourt --8.The Pottery, Philip P. Betancourt --9.The Ground and Chipped Stone Tools, Heidi M.C. Dierckx --10.The Faunal Remains, David S. Reese --11.Arboriculture at Aphrodite's Kephali, Evi Margaritis --DISCUSSION AND INTERPRETATION --12.Hillforts and Watchtowers, Philip P. Betancourt --13.The Place of Aphrodite's Kephali in the Early Development of Fortifications, Philip P. Betancourt --14.The Significance of Aphrodite's Kephali, Philip P. Betancourt.